Application of the Principle of Commercial Exit from Financial Distress in Corporate Bankruptcy Applications and its Implications for Creditor Protection - Rindi Elina; Didik Suhariyanto; Puguh Aji Hari Setiawan (Ilmu Hukum Prima (IHP), 2025)
This research is motivated by the increasing misuse of bankruptcy mechanisms in Indonesia, where solvent debtors exploit bankruptcy as a strategy to evade obligations rather than as a genuine solution for financial distress. The study aims to analyze the regulation of corporate bankruptcy applications that reflect the principle of Commercial Exit from Financial Distress and to examine creditor protection in cases that deviate from this principle. Using a normative juridical approach through statute, case, and conceptual methods, this research relies on primary legal materials including Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations and two court decisions: Number 04/Pdt.Sus-Pailit/2023/PN Niaga Medan (PT Ricky Kurniawan Kertapersada) and Number 41/Pdt.Sus-Pailit/2025/PN Niaga Central Jakarta (PT Teknik Lancar Mandiri). The analysis was conducted qualitatively using sociological interpretation to link legal norms with judicial practice. The findings reveal that Indonesia’s bankruptcy system remains formalistic because it does not apply an insolvency test as a substantive basis for determining financial failure. The PT RKK case demonstrates bankruptcy abuse to avoid debt, while the PT TLM case exemplifies fair application of the Commercial Exit from Financial Distress principle. Hence, reform of bankruptcy law is essential to achieve substantive justice and equitable legal protection for creditors. Penelitian ini menggunakan metode hukum normatif dengan pendekatan yuridis normatif, melalui statute approach, case approach, dan conceptual approach. Bahan hukum primer yang digunakan meliputi peraturan perundang-undangan dan dua putusan pengadilan, yaitu Putusan Nomor 04/Pdt.Sus-Pailit/2023/PN Niaga Medan (PT Ricky Kurniawan Kertapersada) dan Putusan Nomor 41/Pdt.Sus-Pailit/2025/PN Niaga Jakarta Pusat (PT Teknik Lancar Mandiri). Analisis dilakukan secara kualitatif menggunakan metode interpretasi sosiologis untuk menemukan relevansi norma hukum dengan penerapannya di pengadilan. Hasil penelitian menunjukkan bahwa sistem kepailitan Indonesia masih bersifat formalistik karena belum menerapkan insolvency test sebagai dasar substantif. Kasus PT RKK menunjukkan penyalahgunaan mekanisme pailit untuk menghindari kewajiban, sedangkan PT TLM mencerminkan penerapan prinsip Commercial Exit from Financial Distress secara adil dan proporsional. Oleh karena itu, reformasi hukum kepailitan diperlukan untuk memastikan keadilan substantif dan perlindungan hukum kreditur secara seimbang.